Persepsi Generasi-Z tentang Political Amateur dalam Pilkada Kota Bengkulu 2024 - Hutabarat, Preiz Paskah; Widiastuti, Wahyu; Martadireja, Sonde (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
Political Amateur or amateur politics is often associated with individuals who enter the world of politics without having adequate experience or knowledge. This research aims to explore the perception of Generation-Z towards the political amateur phenomenon that emerged in the Regional Head Election (Pilkada) of Bengkulu City 2024, focussing on one of the candidates for deputy mayor, Nuragiyanti Dewi Permatasari, M.Arch. Generation Z, which is now a potential group of voters, has different political views and values from the previous generation. Through a descriptive qualitative approach with the constructivism paradigm, this study uses an in-depth interview method to identify attitudes, judgements and reasons that underlie the perception of generation-Z towards Nuragiyanti Dewi Permatasari as a political amateur, as well as how the candidate's educational background and political experience affect the acceptance of the younger generation. Overall, despite the challenges related to the lack of political experience, the opportunity for Nuragiyanti to gain support from generation Z is very wide open if he is able to utilise technology, transparency, and active involvement with social and environmental issues. The use of social media by Nuragiyanti to convey its vision, mission, and campaign programs transparently and directly to young voters is considered crucial to build a positive image and show commitment to openness. The results of this study provide insight into how generation Z views new leader candidates in the political world and what are the factors that affect their decision to vote in the 2024 Regional Election.